Assessment of tissue oxygen tension: comparison of dynamic fluorescence quenching and polarographic electrode technique - Shaw, Andrew D (BioMed Central, 2002)
INTRODUCTION AND METHODS: Dynamic fluorescence quenching is a technique that may overcome some of the limitations associated with measurement of tissue partial oxygen tension (PO(2)). We compared this technique with a polarographic Eppendorf needle electrode method using a saline tonometer in which the PO(2) could be controlled. We also tested the fluorescence quenching system in a rodent model of skeletal muscle ischemiahypoxia. RESULTS: Both systems measured PO(2) accurately in the tonometer, and there was excellent correlation between them (r(2) = 0.99). The polarographic system exhibited proportional bias that was not evident with the fluorescence method. In vivo, the fluorescence quenching technique provided a readily recordable signal that varied as expected. DISCUSSION: Measurement of tissue PO(2) using fluorescence quenching is at least as accurate as measurement using the Eppendorf needle electrode in vitro, and may prove useful in vivo for assessment of tissue oxygenation.